Hepatitis C transmission from viremic donors in hematopoietic stem cell transplant. Issue 6 (4th November 2014) - Hsiao, H.‐H.; Liu, Y.‐C.; Wang, H.‐C.; Wu, C.‐H.; Cho, S.‐F.; Hsu, J.‐F.; Tsai, H.‐J.; Hsiao, S.Y.; Chang, C.‐S.; Lin, S.‐F.; Liu, T.‐C.; Chuang, W.‐L.; et al.
Abstract Transmission of hepatitis C virus (HCV) to recipients of hematopoietic stem cell transplant (HSCT) occurs frequently from HCV viremic donors and causes complications. Here, we report the outcomes of 3 cases from our 265 allogeneic HSCTs, whose donors had HCV infections. Successful prevention of HCV transmission was noted in 1 recipient by pretreatment of the donor with peginterferon/ribavirin to undetectable levels of HCV viremia before stem cell harvest. This case stressed the important role of effective antiviral therapy and HCV RNA seronegativity before cell harvest for prevention of HCV transmission in HSCT.